Probing the charge injection and dissipation in graphene oxide–epoxy composite. (February 2022) - Jia, Beibei; Chen, Yuqing; Chen, Chengxiang; Li, Yongfei; Ma, Wanli; Zhang, Xuzheng; Zhou, Jun; Wang, Yang; Jiang, Yingye; Wu, Kai
The inorganic filler can modify the electrical and dielectric properties of polymeric composites. However, it is challenging to understand the local charge injection and dissipation in composites through traditional characterization at nanoscale. In this work, we provide a potential mapping of the charge injection and dissipation in the local area of graphene oxide/epoxy resin (GO/EP) composite under various biases by Kelvin probe force microscopy (KPFM) with high spatial resolution. Thus, an improved KPFM experimental setup is used to inject charges at the fixed point to demonstrate surface charge dissipation around the interface between GO and EP. It is found that the charge is more easily injected into the GO/EP nanocomposites and dissipates more quickly in nanocomposite than in neat epoxy resins. Meanwhile, the electrons diffuse more rapidly than holes in pure EP and nanocomposites. The faster charge injection and dissipation of GO/EP composite are ascribed to the filler of GO which has much higher conductivity than that of neat epoxy. This work offers significant insights into the understanding of charge injection and dissipation in dielectric composites.